PTH-096 Monocyte oxidative burst defect in alcoholic hepatitis is resistant to interferon gamma. (22nd June 2015) - Beale, K; Vergis, N; Sadiq, F; Petts, G; Khamri, W; Antoniades, H; Thursz, M
Abstract : Introduction: An important cause of mortality in patients with severe alcoholic hepatitis (SAH) is infection. We and others have found that the oxidative burst response of phagocytic cells to E. coli is impaired in SAH which may contribute to susceptibility to infection. This is analogous to Chronic Granulomatous Disease, an inherited condition caused by a mutation in the enzyme NADPH oxidase which leads to predisposition to recurrent life-threatening infections. Treatment with interferon gamma (IFN-γ) reduces the frequency of severe infections in these patients. We sought to investigate the molecular mechanism underlying the monocyte oxidative burst (mOB) defect in SAH and determine whether IFN-γ can restore this defect in vitro . Method: Peripheral blood mononuclear cells (PBMCs) were isolated from 6 patients with SAH and 4 healthy controls (HCs). Monocytes were isolated from PBMCs using magnetic MACS beads and negative selection. Monocytes were incubated with 50 ng/ml IFN-γ supplemented by 10% healthy serum for 24 h and the mOB to E. coli was quantified by oxidation of fluorogenic rhodamine and flow cytometry as previously described. Western blotting was used to quantify protein using monoclonal antibodies to components of the IFN-γ signalling pathway (pSTAT-1 and negative regulator SOCS-1) and glucose-6-phosphate dehydrogenase (G6PD, which generates NADPH substrate required for NAPDH oxidase function), in the monocytes of HCs and AH patients. G6PD enzyme activity was measured using a colorimetric kit. Quantitative PCR was used to determine expression of STAT-1 in monocytes stimulated for 24 h in 50 ng/ml IFN-γ. Results: Surprisingly, SAH mOB defect was resistant to 24 h' stimulation by 50 ng/mlIFN-γ. The level of unstimulated phosphorylated STAT-1 protein, a transcription factor activated by IFN-γ signalling was significantly reduced in monocytes of SAH patients compared to healthy controls (pSTAT-1: housekeeping gene 0.90 HC vs 0.14 SAH, p < 0 .05). q-PCR confirmed STAT-1 expression following stimulation with IFN-γ was significantly reduced in SAH compared to HCs (ΔCT 0.97 HC vs SAH 0.54, p < 0 .05). The level of SOCS-1 protein was significantly increased in monocytes of SAH patients compared to HCs (SOCS-1: housekeeping gene 0.98 HC vs 2.24 AH, p < 0 .05). There was no difference in G6PD enzyme activity or protein expression between groups. Conclusion: Our study suggests that elevated levels of the inhibitory factor SOCS-1 may reduce phosphorylation and activation of STAT-1. Reduced pSTAT-1 may explain the resistance to IFN-γ observed and hence the burst defect in SAH. This work provides a novel insight into the impaired mOB in SAH and furthers our knowledge of the predisposition to infection observed in this patient group. Disclosure of interest: None Declared.